N‐Type Self‐Assembled Monolayer Field‐Effect Transistors and Complementary Inverters. (19th November 2012) - Ringk, Andreas; Li, Xiaoran; Gholamrezaie, Fatemeh; Smits, Edsger C. P.; Neuhold, Alfred; Moser, Armin; Van der Marel, Cees; Gelinck, Gerwin H.; Resel, Roland; de Leeuw, Dago M.; Strohriegl, Peter
Abstract This work describes n‐type self‐assembled monolayer field‐effect transistors (SAMFETs) based on a perylene derivative which is covalently fixed to an aluminum oxide dielectric via a phosphonic acid linker. N‐type SAMFETs spontaneously formed by a single layer of active molecules are demonstrated for transistor channel length up to 100 μm. Highly reproducible transistors with electron mobilities of 1.5 × 10−3 cm2 V−1 s−1 and on/off current ratios up to 105 are obtained. By implementing n‐type and p‐type transistors in one device, a complimentary inverter based solely on SAMFETs is demonstrated for the first time.